Pengaruh Perilaku Follower Investor pada Volatilitas Saham - Untari, Made Dewi Ayu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 1 (2017), 2017)
The purposes of this study are to obtain emperical evidence about the influence of followers investor’s behaviour to the stock volatility and analyze the difference offollowers investor’s betweenindustry sectors producing raw materials,manufacture industry and service industry in the Indonesia Stock Exchange (BEI), during the market crash happened in Indonesia. The population number are 507 companies, while the total sample of 247 companies. Sampling technique used purposive sampling. The analysis technique used was a cross-sectional absolute Deviation (CSADand test One Way ANOVA with Post Hoc Test and Least Significant Difference (LSD. Data shows that the behavior of follower investors has positive effect on the volatility of the current stock market crash occurs. Meanwhile, there was no difference in behavior between the follower investor industrial sectors producing raw materials, the manufacturing sector and the service sector when  the market crash.
Keywords: Perilaku follower investor, volatilitas saham